Levantamento e Informatização dos Tipos Nomenclaturais de Sapotaceae Juss. Existentes no Herbário IAN - Embrapa Amazônia Oriental - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2004)
The present work aims to survey and computerize the nomenclatural types of Sapotaceae, deposited in the collection of the IAN Herbarium of Embrapa Amazônia Oriental, as a subsidy to the Virtual Herbarium of the Amazon. Types constitute the most valuable material in herbaria, and are very important for researchers who depend on them to prepare taxonomic revisions and floras. For identification of the specimens, the original work of the surveyed taxa was located, through Index Kewensis, Flora Neotropica or other sources of information via the Internet. Based on the princeps, the type was classified based on the International Code of Botanical Nomenclature. So far, 173 specimens of Sapotaceae have been registered. The check-list of these types is presented, with their categories (holotype, isotype. etc.), including the registration number in the Herbarium, the specific epithet with the respective author, collector and number, as well as the image of some specimens. The classification presented is up to date, but it is suggested that it be revised by the specialists. The results will be available in the future on the Internet, together with data from the MG, INPA and HAMAB Herbaria. (Project PNOPGIMPEG and Project Dendrogene - Embrapa Amazônia Oriental/DFID).
Survey and Computerization of the Nomenclatural Types of Sapotaceae Juss. Existing in the Herbarium IAN - Embrapa Amazônia Oriental
Keywords: Biodiversidade; Coleções botânicas; Sapotaceae; Taxonomia vegetal; Herbário virtual; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA